The horse-head fiddle and the cosmopolitan reimagination of tradition in Mongolia [ - Marsh, Peter K. (Current research in ethnomusicology, 2009)
Seeks to understand the effects that Western-inspired modernity has had on the nature of cultural tradition in Mongolia, focusing in particular on the development of the horse-head fiddle - an